Borges en el ejercicio de la crítica literaria: A propósito de Inquisiciones y Otras inquisiciones (Segunda parte) - Víquez Jiménez, Alí (2005)
This is the second in a series of three articles dedicated to contrasting the differeces that in the exercise of literary criticism, are said to be bundamental in two books of Jorge Luis Borges, Inquisiciones (1925) and Otras Inquisiciones (1965). In the manner in which the theoretical-literary orientations of Borges have not been made explicit in either of the two books, the exercise consists of deducing the presuppositions that lie beneath the practical criticism of Borges.  The second article concetrates on the existing relationships between.Otras Inquisiciones and the Borgesian literary work griten contemporarily with this book of criticism, and concludes that thereexists and important projection of the preoccupations, ideas and aesthetic proposals of the writer Borges, within Borges as critic: the notion of history, the creation of fundamental symbols, the role of literature as dream space, the position or views of Plato and Aristotle, the conception of the world as a book, the abandonment of the creeds, the impossibility of the overcoming of nothingness.